A Novel Design of Gas System and Develop Culture Medium for the Isolation and Sulfur Reducing Bacteria within Short Time - Adnan Neamah Albaidani; Fouad Hussein Kamel; Abeer Younis Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The current study has developed a proprietary system and a special device for the supply of oxygen-freenitrogen gas with a mixture of carbon dioxide and 80:20% according to the laboratory conditions required forthe growth of sulfur-reducing bacteria. To find the best medium that fits the bacteria in those environmentswith shortening incubation period, the new medium developed is available in the specification of plantingrich in energy sources, minerals and vitamins and high reduction ability promotes the early growth of sulfurreducing bacteria .